The German Young Olympic Athletes' Lifestyle and Health Management Study (GOAL Study): design of a mixed-method study - Mayer Jochen; Schubring Astrid M; Schnell Alexia; Giel Katrin E; Diehl Katharina; Thiel Ansgar; Zipfel Stephan; Schneider Sven (BMC, 2011)
Abstract Background In order to perform at top levels, elite athletes have to both protect and risk their health at the same time. Adolescent elite athletes have the additional challenge of coping with substantial physical, psychological and social transformations. The contradictory phenomenon of protecting and risking the adolescent athletes' health in sports challenges the development of health promotion and protection strategies. The GOAL Study (German Young Olympic Athletes' Lifestyle and Health Management Study) analyzes the individual and organizational management of health in adolescent elite sports. Methods/design We combine quantitative and qualitative approaches in a mixed-method study. This allows us to gather a broad range of representative information on squad athletes from all Olympic disciplines as well as in-depth information on four selected Olympic disciplines (artistic gymnastics, biathlon, handball and wrestling). Within the quantitative section we attempt to identify the young athletes' health and nutrition behavior, their subjective health state and their lay health representations, health-related social networks, and structures of medical attendance. 1138 national team level athletes born between 1992 and 1995 from 51 Olympic disciplines responded to the questionnaire (response rate: 61,75%). The qualitative section investigates the meaning and relevance of health and nutrition within the athletes' sports specific surroundings, the impact of biographic backgrounds on individual health behavior, and sports specific cultures of health, nutrition and risk. We interviewed 24 athletes and 28 coaching and medical experts, and carried out 14 multi-day participant observations at training sessions and competitions. Conclusions The studies' results will serve as the basis for developing tailored health promotion strategies to be in cooperation with German elite sports associations.